Telehealth for genetic counseling: A systematic evidence review. Issue 5 (6th August 2021) - Danylchuk, Noelle R.; Cook, Lola; Shane‐Carson, Kate P.; Cacioppo, Cara N.; Hardy, Melanie W.; Nusbaum, Rachel; Steelman, Susan C.; Malinowski, Jennifer
Abstract: Telehealth options, such as telephone counseling or videoconferencing, for service delivery in genetic counseling are becoming more widely accepted. However, until now, there has not been a systematic review of the literature focused specifically on genetic counseling outcomes for telehealth. We performed a systematic evidence review to compare telehealth genetic counseling (THGC), including videoconferencing and telephone counseling, across specialties to in‐person genetic counseling (IPGC) for a range of outcomes specific to patient and provider experiences and access to care. Several biomedical databases were queried up to January 11, 2021, to identify original research evaluating THGC. Through this search, 42 articles met the inclusion criteria including 13 randomized controlled trials and 29 non‐randomized observational studies encompassing 13, 901 patients. Most included studies focused only on cancer genetic counseling; however, adult, pediatric, and prenatal specialties were also represented. The majority of studies evaluated patient and/or access to care outcomes. Though most studies reported high patient satisfaction with THGC, as well as comparable rates of trust and rapport, confidence in privacy, health behavior changes, and psychosocial outcomes, few represented diverse populations. Data of provider experiences were limited and varied with more disadvantages noted compared with patient experiences, particularly in studies involving telephone genetic counseling. Studies consistently reported a decrease in the patients' costs and time required for travel when patients are seen via THGC compared to IPGC with a similar reduction in costs to the health system. Overall, results from our evidence synthesis suggest THGC is non‐inferior or comparable to IPGC across many domains, even considering that many of the studies included in this review were conducted with telehealth systems, notably videoconferencing, that were less robust and reliable than what is available today. There are notable limitations within this body of literature, leading to potential uncertainty in the generalizability of our analysis. We outline several recommendations for future studies.